Beckman Model AB-3X-4 Auto Bridge - Commercial Photographic Company (1950)
Industrial Instruments was a manufacturer of solution conductivity analyzers and other industrial instruments. Beckman Instruments acquired the Cedar Grove, New Jersey-based company in 1965.
Keywords: Scientific apparatus and instruments; Beckman Instruments, Inc.